2013
DOI: 10.9738/cc161.1
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Has a Close Association With Gangrenous Appendicitis in Patients Undergoing Appendectomy

Abstract: The purpose of this study was to clarify the clinical features most closely associated with gangrenous appendicitis. From among 314 patients who had undergone open appendectomy in our collected database, 222 for whom sufficient data were evaluable were enrolled. The results of univariate analysis revealed that age (≤40/>40 years), sex (female/male), fever (≤37°/>37°C), the serum levels of C-reactive protein and albumin, the Glasgow prognostic score (0, 1/2), and the neutrophil-to-lymphocyte ratio (NLR) (≤8/>8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
120
8
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(150 citation statements)
references
References 31 publications
15
120
8
7
Order By: Relevance
“…The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy are 88.0%, 71.4%, 78.5%, 83.3%, and 80.4% consecutively. 11,13,20 It can be concluded that in this study, the cut-off point for NLR was no better than the other studies because the sensitivity and specificity numbers were still lower. As for the cut-off point for CRP is still superior to the study conducted by Moon H in terms of sensitivity.…”
Section: Exclusion Criteriamentioning
confidence: 62%
“…The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy are 88.0%, 71.4%, 78.5%, 83.3%, and 80.4% consecutively. 11,13,20 It can be concluded that in this study, the cut-off point for NLR was no better than the other studies because the sensitivity and specificity numbers were still lower. As for the cut-off point for CRP is still superior to the study conducted by Moon H in terms of sensitivity.…”
Section: Exclusion Criteriamentioning
confidence: 62%
“…Ishizuka and colleagues found a significant association between NLR and severity of acute appendicitis. Neutrophil/lymphocyte ratio was significantly different between catarrhal, phlegmonous and gangrenous appendicitis groups [19]. Markar and colleagues were found a higher level of NLR in AA.…”
Section: Discussionmentioning
confidence: 96%
“…[8] Although several studies have explored the utility of NLR in the diagnosis and prognosis of inflammatory and malignant diseases, very rarely has NLR been used in the diagnosis of AMI. [9][10][11] In the present study, the diagnostic capacity of NLR was evaluated and compared to traditional parameters in such patients.…”
Section: Introductionmentioning
confidence: 99%